Determining the frequency of serious adverse reactions of inactive SARS-COV-2 vaccine - Kaya, Ferit; Pirincci, Edibe (Sage Publications Inc, 2021)
BACKGROUND: Vaccines are a new combat strategy against COVID-19. The success of a large number of vaccines and the continued development of vaccines will change the course of the current pandemic. OBJECTIVE: The aim of the study was to determine the frequency of serious adverse reactions caused by the administration of inactive vaccine administration on healthcare workers during the COVID-19 pandemic. METHODS: The prospective study was conducted among healthcare professionals working in city a Training and Research Hospital and applied to have the second dose of CoronaVac vaccine. The number of personnel included in the study were 329. The data were recorded in the SPSS 23 program and the chi-square test was used for statistical analysis. RESULTS: The average age of the participants in the study was 35.77 +/- 9.07. Of the participants, 28.1% were physicians. The frequency ratio of those who stated that they had serious adverse reactions after vaccination was 33.2%. Three most common systemic serious adverse reactions were headache, state of sleep/fatigue, and nausea and vomiting respectively. Serious adverse reactions occurred within 1.14 +/- 04 days after vaccine administration. The average duration of serious adverse reactions was determined as 1.68 +/- 0.77 days. 62.2% of the participants with serious side effects were women (p < 0.001). Of the participants who had serious adverse reactions, 77.5% were health care professionals (p < 0.01). CONCLUSION: No life-threatening serious adverse reactionwas determined regarding the CoronaVac vaccine administered in this study. However, local serious adverse reactions, nausea/vomiting, fever and sleepiness/fatigue occurred frequently. Further studies are required on the newly introduced vaccine.
Keywords: Pandemic; healthcare professionals; fever; injection site; hospital; COVID-19